Strategies towards a compact XUV free electron laser adopted for the LUNEX5 project. Issue 4 (21st February 2016) - Couprie, M. E.; Labat, M.; Evain, C.; Szwaj, C.; Bielawski, S.; Hubert, N.; Benabderrahmane, C.; Briquez, F.; Chapuis, L.; Marteau, F.; Valléau, M.; Marcouillé, O.; et al.
Abstract : More than 50 years after the laser discovery, X-ray free electron lasers (FEL), the first powerful tuneable, short pulse lasers in the X-ray spectral range, are now blooming in the world, enabling new discoveries on the ultra-fast dynamics of excited systems and imaging. LUNEX5 demonstrator project aims at investigating paths towards advanced and compact FELs. Two strategies are adopted. The first one concerns the FEL line where seeding and echo harmonic generation are implemented together with compact cryogenic in-vacuum undulators. In the second one, the electron beam is no longer provided by a conventional linear accelerator but by a laser plasma process, while a necessary particular electron beam manipulation is required to handle the electron properties to enable FEL amplification.